The Foliate Mask in Vernacular Material Culture from Medieval to Modern Norway - Lykke, Karen V; Ohrvik, Ane (Journal for the Study of Religion, Nature and Culture, 2023)
In this article, we explore the contexts and appearances of what we argue is a Norwegian version of the Green Man – the Glibb – in vernacular settings. We also discuss the figure’s possible meanings in Norwegian secular culture. Most of the objects are part of the digital artifact collection called DigitaltMuseum (Digital Museum), which is a common database for Norwegian and Swedish museums and collections. Our collection and analysis of this material provides an initial step toward documenting the figure’s appearances and uses beyond the ecclesial material culture; however, it does not represent an exhaustive list of sources. We investigate the appearance of this particular ‘Green Man’ figure, discussing its material form and iconographical features and analysing its placement and occurrence. We argue that the Glibb’s ambiguous and flexible imagery is also a flexible symbol. Over the centuries, such symbols can enter into new constellations and interpretations of meaning with is new generation that continues to use their material forms.